Strategi Pemasaran Produk Olahan Lidah Buaya Desa Katongan, Kecamatan Nglipar, Kabupaten Gunungkidul, D.I Yogyakarta - Wiranata, Ferdinandus Edwin (Jurnal Atma Inovasia, 2022)
Kuliah Kerja Nyata (KKN) started from April to May 2021. The distribution of locations for the implementation of KKN 79 includes Kulon Progo Regency and Gunungkidul Regency, Yogyakarta Special Region Province. In its implementation, KKN 79 Unit N Group 69 is located in Katongan Village, Nglipar District, Gunungkidul Regency. Broadly speaking, Katongan Village has the main potential in the field of aloe vera processing. Based on observations, this village already has a business in processed aloe vera products, such as beverage products from aloe vera and chips from aloe vera. However, this activity has constraints on the marketing of the resulting product so it requires a marketing strategy. The purpose of implementing the Group 69 Community Service Program is to provide information on how to market the aloe vera product so that it can compete with other products. The compilation of KKN outcomes is carried out by collecting (secondary) data, presenting qualitative reports that are descriptive-analysis and method of documentation. The result of the dedication of KKN 79 Unit N Group 69 are processed products of aloe vera that can be marketed from inside and outside the village with various form of effective marketing strategies in helping the people of Katongan Village.